Religion, literature, and politics in post-Reformation England, 1540-1688 - Hamilton, Donna B.; Strier, Richard (Cambridge University Press, 1996)
This collection of essays by historians and literary scholars treats English history and culture from the Henrician Reformation to the Glorious Revolution as a single coherent period in which religion is a dominant element in political and cultural life. It seeks to explore the centrality of the religion-politics nexus for this whole period through examining a wide variety of literary and non-literary texts, from plays and poems to devotional treatises, political treatises and histories. It breaks down normal distinctions between Tudor and Stuart, pre- and post-Restoration periods to reveal a coherent (though not all serene and untroubled) post-Reformation culture struggling with major issues of belief, practice and authority